Analisis Strategi Pemasaran Dalam Persaingan Bisnis Kuliner (Studi kasus pada Geprek Bensu, Pengasinan Bekasi Timur) - Selatika Saputri; Diana Prihadini (JAMBIS : Jurnal Administrasi Bisnis, 2021)
The marketing strategy is one of the strategies chosen by culinary entrepreneurs to develop their culinary business. The culinary business in East Bekasi has developed quite rapidly. Up to now, the competition of culinary business in East Bekasi is so tight that the number of crushed crispy chicken food outlets is growing continually, such as the competitor next to Geprek Bensu Pengasinan, namely I Am Geprek Bensu. Geprek Bensu is a fast food franchise of Crushed Crispy Chicken, owned by actor Ruben Onsu as the CEO of PT Onsu Pangan Perkasa (OPP) which was established on April 17, 2017. This research used descriptive qualitative method. The data were collected through observation, interview, and documentation. Based on the results of the research to be analyzed, the Marketing Strategy carried out by Geprek Bensu Pengasinan in the culinary business competition has been relatively good as evidenced by the existence of clear food and beverage menu products and supportive promotional strategies. However, there were also some notes such as higher price for its food menu, inadequate facilities and ineffective services.